Effects of Age and Sex on Aerobic Fitness, Sprint Performance, and Change of Direction Speed in High School Athletes. Issue 5 (12th May 2023) - Hackett, Daniel A.; He, Wu; Fleeton, Jennifer R.M.; Orr, Rhonda; Sanders, Ross H.
Abstract: Hackett, DA, He, W, Fleeton, JRM, Orr, R, and Sanders, RH. Effects of age and sex on aerobic fitness, sprint performance, and change of direction speed in high school athletes. J Strength Cond Res 37(5): 325–331, 2023—The purpose of this study was to examine the effects of sex and age on aerobic fitness, sprinting performance, and change of direction speed (CODS) in high school athletes, with consideration for maturity. This cross-sectional study involved 2, 132 adolescents (1, 415 male and 717 female athletes) aged 12.0–15.9 years. Assessment of aerobic fitness using the 20-m multistage fitness test (20MSFT) and 20-m sprint and CODS using the 505 test was performed. For the analysis of data, subjects were separated into 4 age groups: U/13 years, U/14 years, U/15 years, and U/16 years. Estimated age at peak height velocity was a covariate in the data analysis to control for maturity status. Compared with female athletes, male athletes had superior performances at all age groups in 10-m sprint ( p < 0.001, effect size [ES] = >−0.44), 20-m sprint ( p < 0.001, ES = >−0.55), and 505 test ( p < 0.001, ES = >−0.41). Female athletes performed better than male athletes in 20MSFT at U/13 ( p < 0.01, ES = −0.22); however, male athletes had better performances at U/15 ( p < 0.01, ES = 0.27) and U/16 ( p < 0.001, ES = 0.67). At each consecutive age group, male athletes improve their performances in 20MSFT and sprints and at U/14 and U/16 in the 505 test ( p < 0.001, ES > −0.37). Female athletes showed no improvement in the 20MSFT and 505 test between U/13-U/16 but showed improved sprint performance at U/15 compared with U/13 and at U/16 compared with U/14 ( p < 0.05). This study shows that adolescent male athletes perform consistently better than female athletes in running-related field-based tests and display continuous improvements across age groups.